The Role of Drug-Induced Sleep Endoscopy with Positive Airway Pressure Titration in the Individualized Treatment of Obstructive Sleep Apnea: A Report of Three Illustrative Cases - Li PJ; Gong LJ; Huang ZY; Zhang X; Liu D; Liang ZA (Nature and Science of Sleep)
Pei-Jun Li,1,* Lin-Jing Gong,1,* Zi-Yang Huang,2 Xiang Zhang,3 Dan Liu,1 Zong-An Liang1 1Department of Pulmonary and Critical Care Medicine, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, West China School of Medicine/West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Department of Anesthesiology, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pei-Jun Li, Department of Pulmonary and Critical Care Medicine, West China Hospital, Sichuan University, No. 37 Guoxue Road, Chengdu, Sichuan, 610041, People’s Republic of China, Email kakasinp526@163.comPurpose: Drug-induced sleep endoscopy with positive airway pressure titration (DISE-PAPT) can assess the effect of varying positive pressure levels on upper airway collapse in patients with obstructive sleep apnea (OSA) under simulated sleep condition. But it remains unclear whether DISE-PAPT can facilitate the development of personalized therapeutic interventions for OSA and further improve the therapeutic efficacy.Patients and Methods: We present three adult patients with severe OSA exhibiting distinct clinical profiles: one case of continuous positive airway pressure (CPAP) treatment failure, one case of intolerance to high CPAP, and one case of psychological resistance to CPAP therapy.Results: According to the DISE-PAPT evaluation findings, CPAP combined with positional therapy was administered in Case 1. CPAP with surgical management was performed in Case 2, resulting in significant therapeutic improvements. Additionally, real-time DISE-PAPT visualization of CPAP-mediated upper airway patency restoration enhanced CPAP adherence in Case 3.Conclusion: The personalized treatment strategies based on the DISE-PAPT technique hold promise for improving the overall therapeutic efficacy and adherence among patients with OSA.Keywords: DISE-PAPT, CPAP, obstructive sleep apnea, therapy